Determinants of R&D Disclosures of Nasdaq-Listed Biotechnology Firms - TAN, Pearl Hock Neo (Institutional Knowledge at Singapore Management University, 2005)
This study investigates the determinants of discretionary research and development (R&D) disclosures of biotechnology firms listed on the NASDAQ. Our study proposes that firms with higher levels of information asymmetry are more likely to disclose information about R&D than firms with lower levels of information asymmetry. However, proprietary costs thwart the incentives for firms to adopt a policy of full disclosure on R&D. We find results that are consistent with our propositions. Firms that have higher levels of information asymmetry that are proxied by higher growth options, higher concentrations of R&D expenditures and dependence on equity funding (as opposed to debt funding) are found to have higher levels of R&D disclosures. Further, our results show that firms that have lower proprietary costs through patent protection or through having a size advantage disclose more information than other firms.